EVERYONE CAN BE A LEADER: Pengembangan Organisasi Melalui Pelatihan Leadership dan Public Speaking - Dian Dwi Nur Rahmah; Dila Adelina Greenfieldslia; Adinda Alya Amanullah; Asiya Asiya; Silva Linggi Allo; Tasya Kamila; Muhammad Hairul Saleh; Bungai Bungai; Yusrinda Prababeni (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2024)
The success of an organization depends on the quality of the members in it and how they develop it. Members of the Informatics Engineering Student Association (HIMA-TI) STMIK WICIDA Samarinda are known to have difficulties in leadership and public speaking skills, so this affects the quality of the members and hinders organizational success. The purpose of this training is to increase the knowledge and skills of leadership and public speaking of members of HIMA-TI STMIK WICIDA Samarinda in order to increase organizational success. The description of the design and training materials obtained based on this is an experimental research method that uses a direct learning process accompanied by discussions and case studies. There was an increase in the results of the cognitive evaluation of the training participants which showed an increase with a pre-test cognitive evaluation score of 57.58 participants and a post-test cognitive evaluation result of 73.03 percent, so that the increase in understanding of the participants after the training was carried out by 15.45 percent. The scale shows the results of the training that there has been an increase in the knowledge of the training participants regarding leadership and public speaking skills, especially in terms of organization.Keberhasilan sebuah organisasi tergantung pada kualitas anggota di dalamnya dan bagaimana cara mereka mengembangkannya. Anggota Himpunan Mahasiswa Teknik Informatika (HIMA-TI) STMIK WICIDA Samarinda diketahui memiliki kesulitan dalam kemampuan leadership dan public speaking, sehingga ini berpengaruh pada kualitas para anggota dan menghambat keberhasilan organisai. Tujuan dari pelatihan ini adalah untuk meningkatkan pengetahuan dan keterampilan leadership dan public speaking para anggota HIMA-TI STMIK WICIDA Samarinda agar dapat meningkatkan keberhasilan organisasi. Gambaran rancangan dan materi pelatihan didapatkan berdasarkan ini adalah metode penelitian eksperimen yang menggunakan proses pembelajaran secara langsung disertai dengan diskusi dan studi kasus. Terjadi peningkatan pada hasil evaluasi kognitif peserta pelatihan yang menunjukkan kenaikan dengan nilai evaluasi kognitif pre- test sebesar 57,58 peser dan hasil evaluasi kognitif post-test sebesar 73,03 persen, sehingga peningkatan pemahaman pada peserta setelah dilakukan pelatihan sebesar 15,45 persen. Skala tersebut menunjukkan hasil pelatihan bahwa terjadi peningkatan terhadap pengetahuan peserta pelatihan mengenai kemampuan leadership dan public speaking terutama dalam hal berorganisasi.